The gamification features' effect on the training effectiveness in organizational context - Caixado, Duarte Manuel Farinha (2019)
The learning approach and trainees’ expectations change throughout time due to generational characteristics, furthering the need to innovate new ways to train employees within organizations. Taking advantage of the technological development and digital orientation of the current workforce, gamification has proven to be an effective approach to learning purposes. This method incorporates game design elements into non-game environments, such as learning scenarios, aiming to improve motivational levels and, therefore, promote training effectiveness. The present research aims to study user experience satisfaction and how could it impact training effectiveness. Furthermore, training motivation is analyzed as a mediator on this relation, as well as work engagement and open-mindedness in moderation roles. A sample of 128 respondents allowed researchers to understand the strong correlation between gamification, measured through the user experience satisfaction, and training effectiveness. Additionally, the research showed that training motivation is crucial in making the first relationship happen. Moreover, work engagement and open-mindedness do not seem to have significant influence as moderators in the relationship described. To build up gamified application for training, many variables should be taken into consideration when choosing the right gamification elements to include. These variables include concepts such as participants’ needs in regards to course content and training purpose. Additionally, these processes require organizations to be aware of the Human Resources policies and practices that should be adjusted to improve training and development methodologies.